A symphony of choices : how mentorship taught a manager decision-making, project management and workplace engagement -- and saved a concert season - Leonard, Gerald J. (John Wiley & Sons, Inc., 2023)
"A Symphony of Choices follows Jerry Hall, the new Symphony Orchestra manager at a prestigious symphony who is concerned about all the challenging plans for the new season: the 100th anniversary of the symphony. Because he's faced with handling many professional and personal challenges every day, his partner is not exactly thrilled about his new position. Jerry has played with the symphony for twenty years, thus gaining great understanding as a symphony musician. One day, Jerry connects with one of his previous college professors of effective decision making and project portfolio management. The professor agrees to mentor and coach Jerry through the twists and turns of successfully managing through these unprecedented times in his business and personal life. Does he have all the skills necessary for effective decision-making and managing a major symphony's portfolio of multiple projects for the upcoming concert season or will his fear of overcoming challenges hold him back from succeeding? A Symphony of Choices teaches readers from all industries the critical skills of decision-making, overcoming challenges, and succeeding in the face of interconnected adversities."--